2013
DOI: 10.4236/jwarp.2013.54040
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Plankton to a Fresh Water Pulse in a Fresh Water Deprived, Permanently Open South African Estuary

Abstract: This study assessed the influence of a freshwater pulse on selected physico-chemical and biological variables in a permanently open freshwater deprived southern African estuary. In the absence of the freshwater pulse a reverse gradient in salinity was evident with hypersaline (salinity > 40) conditions prevailing in the upper reaches of the estuary. Total chlorophyll-a (chl-a) concentration during this period ranged from 0.25 to 0.60 µg·l (SD ± 1203) and the biomass 21.8 mg·dwt·m −3 (SD ± 196). The total zoopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It has been suggested that S. watermeyeri is a specialist feeder that depends on specific prey, in particular the copepod Pseudodiaptomus hessei , for its survival (Whitfield et al, 2017; Ntshudisane et al, 2021). Based on the assumption that S. watermeyeri is a specialist feeder, the lack of freshwater inflow into the Kariega and Bushmans estuaries has been identified as one of the leading causes for the rarity of this species (Whitfield & Ter Morshuizen, 1992; Whitfield & Bruton, 1996; Whitfield et al, 2017) owing to the adverse effects on invertebrate communities caused by a decrease in freshwater pulses (Froneman & Vorwerk, 2013). Direct competition for resources between S. watermeyeri and S. temminckii has not been confirmed, and competition for food would be unlikely owing to the substantial difference in size between the two species and thus differences in gape size and the prey that would be targeted by each (Tipton & Bell, 1988; Teixeira & Musick, 2001; Manning, Foster & Vincent, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that S. watermeyeri is a specialist feeder that depends on specific prey, in particular the copepod Pseudodiaptomus hessei , for its survival (Whitfield et al, 2017; Ntshudisane et al, 2021). Based on the assumption that S. watermeyeri is a specialist feeder, the lack of freshwater inflow into the Kariega and Bushmans estuaries has been identified as one of the leading causes for the rarity of this species (Whitfield & Ter Morshuizen, 1992; Whitfield & Bruton, 1996; Whitfield et al, 2017) owing to the adverse effects on invertebrate communities caused by a decrease in freshwater pulses (Froneman & Vorwerk, 2013). Direct competition for resources between S. watermeyeri and S. temminckii has not been confirmed, and competition for food would be unlikely owing to the substantial difference in size between the two species and thus differences in gape size and the prey that would be targeted by each (Tipton & Bell, 1988; Teixeira & Musick, 2001; Manning, Foster & Vincent, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The large number of OTUs from the calanoid copepod P. hessei in the feces of S. watermeyeri was clearly linked to low freshwater inflow into this estuary during the study period. The zooplankton community of the Bushmans Estuary has been poorly studied, but during low or zero river flow periods in the Kariega Estuary, P. hessei dominates the zooplankton community (up to 76% by number), this can change following river flooding when another calanoid, Acartia longipatella , becomes more abundant (Froneman and Vorwerk, 2013). Possible dietary switches by S. watermeyeri according to changes in copepod species composition in the zooplankton community have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Both are marine-dominated, permanently open systems (Mwale et al, 2014), a type of estuary that is comparatively rare in South Africa (Whitfield & Baliwe, 2013). Salinity in these estuaries is similar to that of the ocean (Teske & Wooldridge, 2003), but hypersaline conditions may develop during episodic droughts because of evaporative loss (Froneman & Vorwerk, 2013; Grange et al, 2000).…”
Section: Introductionmentioning
confidence: 99%